2015
DOI: 10.1038/ejcn.2014.272
|View full text |Cite
|
Sign up to set email alerts
|

Functional cobalamin (vitamin B12) deficiency: role of advanced age and disorders associated with increased oxidative stress

Abstract: Functional Cbl deficiency is associated with disorders marked by increased oxidative stress particularly in the elderly; it occurs even when Cbl levels are high and is not consistently corrected with high-dose cyanocobalamin therapy. Thus, current approaches to recognizing and managing this disorder may be inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 53 publications
1
32
0
1
Order By: Relevance
“…The serum biomarker analyses included in this study were Serum B12, C‐reactive protein (CRP) (a nonspecific inflammatory marker), Homocysteine (HCys), and Methylmalonic Acid (MMA). HCys and MMA levels were determined to more accurately assess the vitamin B12 status . Although blood analysis may reflect levels of vitamin B12 that are in the normal range, elevated levels of cobalamin metabolites including MMA or HCys may be the first signs of deficiency .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The serum biomarker analyses included in this study were Serum B12, C‐reactive protein (CRP) (a nonspecific inflammatory marker), Homocysteine (HCys), and Methylmalonic Acid (MMA). HCys and MMA levels were determined to more accurately assess the vitamin B12 status . Although blood analysis may reflect levels of vitamin B12 that are in the normal range, elevated levels of cobalamin metabolites including MMA or HCys may be the first signs of deficiency .…”
Section: Methodsmentioning
confidence: 99%
“…HCys and MMA levels were determined to more accurately assess the vitamin B12 status . Although blood analysis may reflect levels of vitamin B12 that are in the normal range, elevated levels of cobalamin metabolites including MMA or HCys may be the first signs of deficiency . It has been reported that 7%‐30% of people over the age of 60 have vitamin B12 deficiency, yet their presentation is ‘subclinical’ and is known as ‘functional cobalamin deficiency’ .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…B. Cyanocobalamin 500-1000 µg/Tag) kann durch Mangel entwickeln kann. Dabei ist bemerkenswert, dass bei älteren Patienten mit einer zusätzlichen Belastung durch oxidativen Stress auch Serumspiegel von Cobalamin im höheren Normalbereich (> 800 pg/ml) nicht vor einem Anstieg von MMA und/oder Homocystein schützen können [36]. Da Cobalamin sehr oxidationsempfindlich ist, kann es durch intrazellulären oxidativen Stress inaktiviert werden.…”
Section: Bedarf Und Resorptionunclassified